El papel del capital social en la inteligencia competitiva - ORTOLL ESPINET, Eva; LÓPEZ-BORRULL, Alexandre; CANALS, Agustí; GARCIA ALSINA, Montserrat; COBARSI MORALES, Josep (Revista General de Información y Documentación, 2010)
The concepts of Social Capital and Competitive Intelligence have been studied as a resource in the organizations to create value through the processes of capture, analysis, creation and transfer of information and knowledge. Each of them plays a central part in several theoretical frameworks coming from different disciplines and approaches. The increasing relevance of Social Networks in Information Management and Competitive Intelligence points to the need of developing an integrated referential framework. The purpose of this paper is to provide some guidelines that simplify the analysis and the optimisation of the organization external social network, and the resources derived from this relationship in order to apply them to the competitive intelligence process. Firstly, the Competitive Intelligence and Social Capital concepts are introduced. Finally, a reference framework is described in order to audit the social capital of the organization, to understand which issues of this capital could be taken into account in the CI phases, and to estimate the utility of the knowledge and information derived from the above mentioned capital.
Keywords: Competitive intelligence; Social networks; Social capital; Information behaviour; Information management; Environmental scanning